2021
DOI: 10.3390/molecules26154551
|View full text |Cite
|
Sign up to set email alerts
|

The Therapeutic Potential of Cannabis in Counteracting Oxidative Stress and Inflammation

Abstract: Significant growth of interest in cannabis (Cannabis sativa L.), especially its natural anti-inflammatory and antioxidative properties, has been observed recently. This narrative review aimed to present the state of the art of research concerning the anti-inflammatory activity of all classes of cannabinoids published in the last five years. Multimodal properties of cannabinoids include their involvement in immunological processes, anti-inflammatory, and antioxidative effects. Cannabinoids and non-cannabinoid c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
30
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(31 citation statements)
references
References 125 publications
(194 reference statements)
0
30
0
1
Order By: Relevance
“…CBD can also activate the TRPV1 channel, serotonin 1A (5-HT 1A ) receptors, and opioid receptors [24,172]. CBD has anti-inflammatory, anti-oxidative, anti-epileptic, analgesic, anti-neoplastic, sedative, neuroprotective, and anti-anxiety activities [173][174][175][176][177][178][179][180][181][182][183][184][185][186][187][188]. Moreover, CBD inhibits sebocyte lipogenesis by activating the TRPV4 ion channel that interferes with the pro-lipogenic ERK1/2 MAPK pathway [189].…”
Section: Cannabidiol (Cbd)mentioning
confidence: 99%
“…CBD can also activate the TRPV1 channel, serotonin 1A (5-HT 1A ) receptors, and opioid receptors [24,172]. CBD has anti-inflammatory, anti-oxidative, anti-epileptic, analgesic, anti-neoplastic, sedative, neuroprotective, and anti-anxiety activities [173][174][175][176][177][178][179][180][181][182][183][184][185][186][187][188]. Moreover, CBD inhibits sebocyte lipogenesis by activating the TRPV4 ion channel that interferes with the pro-lipogenic ERK1/2 MAPK pathway [189].…”
Section: Cannabidiol (Cbd)mentioning
confidence: 99%
“…Shi et al confirmed the existence of an imbalance of Th17/Treg cells in psoriasis patients (Shi et al, 2019). CB2R is expressed in B lymphocytes, neutrophils, leucocytes CD8 and CD4, allowing cannabinoids to mitigate the inflammatory response (Graczyk et al, 2021). A previous in vitro study found that the CB2R selective agonist O-1966 activated Tregs and promoted increased IL-10 secretion in the mixed lymphocyte reaction culture supernatant (Robinson et al, 2015).…”
Section: Discussionmentioning
confidence: 92%
“…It is known that the pathogenesis of psoriasis is a result of complex interactions among the neuroendocrine, immune and vascular systems (Armstrong and Read, 2020). Evidence suggests that CB2R plays a critical role in immune modulation and sensory conduction (Sheriff et al, 2020;Graczyk et al, 2021). Although CB2R-mediated immune responses have been observed in other inflammatory skin diseases, including skin wound healing (Wang et al, 2016;Du et al, 2018), allergic contact dermatitis (Karsak et al, 2007) and artificially induced dermatitis (Haruna et al, 2017), little is known about their role in psoriasis.…”
Section: Discussionmentioning
confidence: 99%
“…The first phase (1 hour) involves the release of serotonin and histamine and the second phase (> 1 hour) is mediated by cyclooxygenase products. Continuity between the two phases is provided by kinin (Graczyk et al, 2021). The AEPT and EEPT significantly inhibited the edema formation in both the first and second phases.…”
Section: Discussionmentioning
confidence: 96%